Don't sit on the baby! : the ultimate guide to sane, skilled, and safe babysitting - Bondy, Halley, 1984- (Zest Books, 2022)
"Babysitting is one of the most popular jobs for teens, but caring for kids is not easy. Offering useful tips, this funny, updated guide covers basics any babysitting hopeful needs to know and much more"--